2017
DOI: 10.1161/jaha.117.006071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Deferred Lesions With Angiographically Insignificant Stenosis But Low Fractional Flow Reserve

Abstract: BackgroundData are limited regarding outcomes of deferred lesions in patients with angiographically insignificant stenosis but low fractional flow reserve (FFR). We investigated the natural history of angiographically insignificant stenosis with low FFR among patients who underwent routine 3‐vessel FFR measurement.Methods and ResultsFrom December 2011 to March 2014, 1136 patients with 3298 vessels underwent routine 3‐vessel FFR measurement (3V FFR‐FRIENDS study, ClinicalTrials.gov identifier NCT01621438), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In this issue of JAHA, a subgroup analysis from the 3-Vessel Fractional Flow Reserve for the Assessment of Total Stenosis Burden and its Clinical Impact in Patients With Coronary Artery Disease (3-Vessel FFR-FRIENDS) study provides novel insight into patient outcome data for low-FFR but angiographically insignificant lesions. 18 The majority of the findings by Lee et al are consistent with much of what we already know about FFR, namely, that low-FFR values can be generated in even mild stenoses and that these situations arise most frequently in left main stem and proximal left anterior descending artery lesions. In this patient population, however, in which a low-FFR value may have previously been rationalized away as an indirect sign of high flow and a healthy microcirculation, the (comparatively) unfavorable major adverse cardiac event (MACE) outcomes reported by Lee et al potentially imply an altogether different prognosis.…”
Section: Ffr: a Surrogate Measure Of Coronary Flowsupporting
confidence: 75%
See 1 more Smart Citation
“…In this issue of JAHA, a subgroup analysis from the 3-Vessel Fractional Flow Reserve for the Assessment of Total Stenosis Burden and its Clinical Impact in Patients With Coronary Artery Disease (3-Vessel FFR-FRIENDS) study provides novel insight into patient outcome data for low-FFR but angiographically insignificant lesions. 18 The majority of the findings by Lee et al are consistent with much of what we already know about FFR, namely, that low-FFR values can be generated in even mild stenoses and that these situations arise most frequently in left main stem and proximal left anterior descending artery lesions. In this patient population, however, in which a low-FFR value may have previously been rationalized away as an indirect sign of high flow and a healthy microcirculation, the (comparatively) unfavorable major adverse cardiac event (MACE) outcomes reported by Lee et al potentially imply an altogether different prognosis.…”
Section: Ffr: a Surrogate Measure Of Coronary Flowsupporting
confidence: 75%
“…In this issue of JAHA , a subgroup analysis from the 3‐Vessel Fractional Flow Reserve for the Assessment of Total Stenosis Burden and its Clinical Impact in Patients With Coronary Artery Disease (3‐Vessel FFR‐FRIENDS) study provides novel insight into patient outcome data for low‐FFR but angiographically insignificant lesions . The majority of the findings by Lee et al are consistent with much of what we already know about FFR, namely, that low‐FFR values can be generated in even mild stenoses and that these situations arise most frequently in left main stem and proximal left anterior descending artery lesions.…”
Section: Vulnerable Plaque or Vulnerable End Point?mentioning
confidence: 60%
“…Our study consistently showed that a coronary stenosis with a normal FFR has a low likelihood of having plaques with high-risk features. Therefore, these aforementioned associations shown between plaque features of vulnerability and hemodynamic outcome can also help us understand why revascularization may be safely deferred in lesions with FFR >0.80 [38] and why the event rates were significantly higher in deferred angiographically insignificant lesions in stable CAD patients with low FFR than those with high FFR [39]. In this respect, the benefit of FFR-guided therapy may become evident, at least in part, based on its potential connection with plaque vulnerability/activity shown in both stable and unstable CAD patients in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FFR was an independent predictor of future clinical events in those lesions with angiographically insignificant stenosis. 33) In another substudy, patients with multi-vessel moderate CAD (FFR, 0.81–0.87) showed a comparable risk of clinical events with patients with functionally significant CAD. 34) …”
Section: Pressure Wire Assessment Beyond a Per-vessel Decision For Rementioning
confidence: 97%